Opportunity or Risk? Appraisal and Affect Mediate the Effect of Task Framing on Working Memory Performance in University Students - Chen, Luxi; Qu, Li (Frontiers in Psychology, 2021)
Working memory (WM) is crucial for reasoning, learning, decision-making and academic achievement. In diverse contexts, how a task is framed pertaining to its demands and consequences can influence participants' task performance by modifying their cognitive appraisals. However, less is known about the effect of task framing on WM performance and the mechanisms. This study examined whether opportunity- and risk-focused task framing would influence university students' WM performance by altering their cognitive appraisals and affective experiences. Ninety-seven university students were randomly assigned to one of the three framing conditions (Opportunity, Risk, vs. Null), and received instructions that differed in consequences (gain for top performers, loss for poor performers, vs. null), goals (approach, avoidance, vs. neutral), and feedback on personal competence (adequate, inadequate, vs. null). Challenge and threat appraisals, affect, and WM performance were measured before and after task framing. Results showed that opportunity-focused task framing improved students' WM performance, whilst risk-focused task framing increased threat appraisal and decreased positive affect, and that challenge appraisal was not altered in any condition. Female students were influenced by task framing to a greater extent than were male students. Mediation analysis revealed that the alteration of threat appraisal and the change in positive affect mediated the effect of task framing on WM performance. Findings highlight the important role of modifying cognitive appraisals and affective responses in optimizing cognitive performance.